PLAGIARISM ON ART WORKS COPYRIGHT IN BALI - Tjokorda Udiana Nindhia Pemayun (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2018)
Abstract This thesis focuses comprehensively on plagiarism of copy rights of fine arts in Bali as based on the laws of Republic of Indonesia No 28 Year 2014 on Copy Rights. In this thesis, it is discussed 2 matters, i.e, first, the implementation and protection of copy rights of fine arts in Bali and second, the law enforcement of the breach of copy right of fine arts in Bali. Four legal theories are used : (1) Theory of Legal Certainty, (2) Theory of Legal Protection, (3) Theory of Legal Fairness (4) Theory of Legal System. The relevance of the four theories are used as the analysis tools. The findings of this thesis consist of: in the copy right, there are 2 inherent rights which are economical rights and moral rights. Plagiarism cases or plagiarism towards copy right of fine arts in Bali leads more towards breach of moral rights of the creators. The law enforcements and legal protection of copy rights emphasizes on the offenders of the breach of copy rights of fine arts in Bali who produce and distribute rather than individual users. Plagiarism of creation of fine arts in Bali is not only limited to scientific works and other copy right objects but also towards patent and Brand rights. Keywords: Plagiarism, Copy Rights, Fine Arts.